Analysis of Teacher’s Problems in the Teaching and Learning Process at MA Al-Mustaqim Parepare - Nur Asiza; Ahmad Fauzi; Nanning Nanning; Annisa Ahmad (Universitas Muhammadiyah Barru, 2024)
This research aims to identify the problems faced by teachers in the teaching and learning process at MA Al-Mustaqim Parepare and the methods used to address these issues. The problems encountered include a lack of facilities, low student motivation, and a high workload for teachers. The research method used is descriptive qualitative with data collected through observations, interviews, and documentation. Data analysis was conducted by organizing, interpreting, and concluding the findings based on relevant educational theories. The results show that the main problems faced by teachers are the lack of supporting facilitied, low student participation, and administrative pressures. Teachers use strategies such as personal approaches, creative teaching methods, and enhanced communication with parents to address these issues.